Contemporary Journalism in the US and Germany : Agents of Accountability - Revers, Matthias (Cultural Sociology, 2017)
This book challenges the idea that Western media systems are becoming more American in the digital age, arguing that journalistic cultures are not only significantly different from each other still but also variably open and resistant to change. Drawing upon extensive field research of political reporters and examination of discourses of journalistic professionalism as well institutional analysis, this book finds that occupational norms and values of journalism in the US are vigorously upheld but in fact relatively porous and malleable. In Germany, by contrast, professional boundaries are rather strong and resilient but treated matter-of-factly. Revers argues that this is both a consequence of institutional arrangements of media systems and historically evolved cultural principles of journalism in both countries which mutually constitute each other.- Resumé vydavatel